Hubungan Pola Makan dengan Kejadian Dispepsia Fungsional Pada Mahasiswa Fakultas Kedokteran Universitas Mulawarman: Correlation of Dietary Pattern with the Incidence of Functional Dyspepsia in Students of the Faculty Medicine Mulawarman University - Annisah Nurdwita Ashari; Yuniati Yuniati; Ignatia Sinta Murti (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2022)
Dyspepsia is a term that describes symptomps of upper middle abdominal discomfort. The risk factor that often associated with the incidence of functional dyspepsia is dietary factor. This study was conducted to determine the correlation between dietary pattern with the incidence of functional dyspepsia and this research was analytic using cross sectional approach. Sampling was done by consecutive sampling and the data was collected using questionnaire Rome IV criteria for dyspepsia functional and dietary pattern. It was analysed by Chi-Square test. Out of 173 respondents, 62 (35.8%) had functional dyspepsia. Analysis of dietary pattern and the incidence of functional dyspepsia for meal schedules obtained p-value 0.039(p <0.05) and for types of food and beverages obtained p-value 0.149(p> 0.05). There is a correlation of dietary pattern for meal schedules and functional dyspepsia, no correlation of dietary pattern for types of food and beverages and functional dyspepsia.